Jewelry Art Modeling Design Method Based on Computer-Aided Technology - Yuan Li; Hai Wen (Advances in Multimedia)
In order to improve the effect of jewelry art modeling design, this paper applies computer-aided technology to jewelry art modeling design. Moreover, in order to solve the situation that the given data points do not form a topological rectangular grid, an interpolation algorithm based on triangular BB surfaces is specially studied in this paper. The algorithm automatically triangulates the given scattered data points to establish the topological relationship between the data points, and modified and optimized the triangulation algorithm according to the requirements of jewelry art modeling design. In addition, the improved algorithm can handle the triangulation problem of spatial data points well, and the triangulation speed is fast. The experimental verification shows that the jewelry art modeling design method based on computer-aided technology proposed in this paper can effectively improve the effect of jewelry art modeling design.